Makna Perjuangan Korban Pelanggaran Hak Asasi Manusia - Syauqi Kinan Abrar Al Azzaam; Andalusia Neneng Permatasari (UNISBA Press, 2025)
Abstract. This study analyzes the meaning of human rights violation victims' struggle in the lyrics of